TO SHARE OR TO EXCHANGE: an analysis of the sharing economy characteristics of Airbnb and Fairbnb.coop - Petruzzi, M. A.; Marques, C.; Sheppard, V. (International Journal of Hospitality Management, 2021)
Many organizations seek to position themselves as part of the sharing economy, due to positive conceptual connotations; however, in reality, some may more closely represent the exchange rather than the sharing economy. This research analyses the extent to which Airbnb and Fairbnb.coop represent the sharing economy by examining the characteristics of the sharing economy. We utilize a Sharing Index (SI) and a Sharing Economy Continuum (SEC) to measure each organization's degree of sharing and exchange. The analysis suggests that Fairbnb.coop is a stronger example of the sharing economy than Airbnb. This study offers a more robust characterization of the sharing economy and offers tools to help businesses assess and improve their business practices to more accurately align with the true sharing economy.